RANCANGAN PABRIK PEREMUK DI PT. X DAERAH ISTIMEWA YOGYAKARTA - Muhammad Arifin Nur; Indah Setyowati; Tedy Agung Cahyadi; Sudaryanto; Indun Titisariwati (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2019)
PT. X is one of the companies engaged on andesite mining and crushing. Currently the PT X crusher factory produces 233.3 tons/day of andesite with 2 crusher units, with the demand of 200 - 300 tons/day. The production is expected to be 468.8 tons/day if the third crusher has been built. However, market demand increased to 1100 tons/day. Therefore PT X plans to build a new crusher plant on a new location, because the current location is insufficient if added to any other crusher unit. In the construction of a new crusher plant, a crusher plant design is needed to obtain what tools are needed to obtain the desired production target, and to determine the setting of the crusher. The problem that occurs is that a new crusher plant design is needed for production of 800 tons / day on condition that the product size of -20 + 10 mm is the largest percentage of the whole, more than 28%. In designing a new crusher plant, some data is needed including: material size distribution in the stockyard, effective working time, efficiency of each deck screen, and the location of the establishment of a new crusher plant.